Geo-Spatial Exploration of Tuberculosis in Samarinda Ulu Sub-District, Samarinda City, East Kalimantan - Muh. Amri Arfandi; Muhammad Zakki Saefurrohim; Akhmad Azmiardi; Siswanto; Siti Lutfiyah Ulfa (Panakeia Journal of Epidemiology, 2024)
This research investigates the spatial distribution of tuberculosis (TB) cases in Samarinda Ulu, a sub-district with the second-highest percentage of detected TB cases in Samarinda City. Despite the availability of geographic analysis tools, no prior studies have focused on this area. The study uses a descriptive-analytical, cross-sectional approach, utilizing secondary data from the TB03-SO form for 2023. The total sample includes 323 TB cases, with Google Maps used to locate case coordinates based on respondents’ addresses. Spatial analysis was conducted using QGIS software with overlay, buffer, and nearest neighbor analysis techniques. Results shows that TB cases in Samarinda Ulu are distributed in a clustered pattern (NNI<1), with clusters forming primarily in densely populated areas. The spatial analysis results also indicate that the majority of TB cases spread through close contact with index cases. Teluk Lerong Ilir Village emerges as a TB "hotspot," with the highest concentration of cases. This study suggests strengthening spatial-based TB surveillance and intensifying control efforts, such as enhancing early detection and promoting community-based health education programs in highly populated areas. This would allow health institutions to better target high-risk regions and improve TB prevention and control strategies.